APPLICATION OF HIRUDOTHERAPY AS A METHOD OF TRADITIONAL MEDICINE IN PUBLIC HEALTH PROTECTION - Tozhiakhmedova , Sh.; Gasanova , N. (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
Hirudotherapy is one of the oldest methods of treating various pathological conditions, affecting blood rheology, lipid metabolism, and the human immune system. Treatment with medicinal leeches provides anti-ischemic, neuroprotective, analgesic, anti-inflammatory, and bactericidal effects. The method is widely used in neurology, cardiology, gynecology, dermatology, and the prevention of cardiovascular diseases. Hirudotherapy has minimal contraindications and side effects, which makes it important in modern medicine and public health protection. The article discusses the historical development, therapeutic effects, indications, contraindications, and the significance of hirudotherapy as a method of traditional medicine.